CAR-NK cells: A model for tumor immunotherapy. Literature review - Betancourt-Plaza, John Darowin (2021)
The objective of this review is to describe the biological, immunological, and oncological principles that are associated with the theoretical basis for the use of CAR-NK cells for tumor immunotherapy. Since the discovery of natural killer cells (in English Natural Killer Cells or NK cells), great advances have been made in the understanding of the mechanisms of action, and their functions related to the immune system. This knowledge has led to the development of promising technologies and therapies, such as those based on genetically modified NK cells with chimeric antigen receptors (CARs) called CAR-NK cells that were originally designed for the treatment of different types of cancer, showing potential results in animal models. It is expected that the clinical trials that are being developed will yield positive results for CAR-NK cells, allowing us to know the advantages and disadvantages of this type of immunotherapy.